Education and development : tradition and innovation - Lynch, James; Modgil, Celia; Modgil, Sohan (Cassell, 1997)
This text approaches the subject of education and development on the basis that free universal primary education is a human right, which should be accorded to all children forthwith. This must be provided as a package of benefits, encompassing universal primary education, basic health care and adequate nutrition. The analysis allows for the fact that policies for education are also subject to the influence of broader social philosophies and epistomologies than those solely of the educational system.